ZIF-8 / SnO2 compound as well as preparation method and application thereof

By using ZIF-8/SnO2 composite as NO2 sensor material, using the mesoporous SnO2 nanosphere carrier and ZIF-8 load design, the existing NO2 sensors have solved the problem of high operating temperature and poor selectivity, and achieved accurate low temperature detection and high responsiveness.

CN119775785AActive Publication Date: 2025-04-08SHANGHAI INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411855088.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-08
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing NO2 sensors have high operating temperatures and poor selectivity, making it difficult to achieve accurate low temperature detection.

Method used

The ZIF-8/SnO2 composite is used as the sensor material, and the mesoporous SnO2 nanospheres are used as the carrier, and the internal pores and surface loads ZIF-8 to achieve low temperature detection of NO2.

Benefits of technology

High electrochemical responsiveness and selective detection of NO2 at low temperatures is achieved, and the application problems are avoided due to the limitation of MOF insulation properties, and the impact of humidity on the sensing material is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775785A_ABST
    Figure CN119775785A_ABST
Patent Text Reader

Abstract

The invention relates to a ZIF-8 / SnO2 compound as well as a preparation method and application thereof, the ZIF-8 / SnO2 compound takes mesoporous SnO2 nanospheres as a carrier, and ZIF-8 is loaded on internal pore channels and the surface of the mesoporous SnO2 nanospheres. The diameter of the mesoporous SnO2 nanosphere is 690-720 nm, the aperture of the mesoporous SnO2 nanosphere is 8-9 nm, the specific surface area of the mesoporous SnO2 nanosphere is 78-80 m < 2 >. G <-1 >, the diameter of the ZIF-8 / SnO2 compound is 790-820 nm, the aperture of the ZIF-8 / SnO2 compound is 7-8 nm, and the specific surface area of the ZIF-8 / SnO2 compound is 69-71 m < 2 >. G <-1 >. The preparation method comprises the following steps: preparing mesoporous SnO2 nanospheres; and preparing the SnO2 / ZIF-8 compound. Compared with the prior art, the prepared ZIF-8 / SnO2 compound can be applied to the field of nitrogen dioxide sensing, high electrochemical responsiveness to nitrogen dioxide at a low temperature can be achieved, the situation that application of the ZIF-8 / SnO2 compound in electrochemical sensing is limited due to the insulating property of MOF can be avoided, meanwhile, the influence of humidity on a sensing material is reduced, and the application prospect is wide. Therefore, the selective response to nitrogen dioxide is improved to a great extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal organic framework materials, and in particular to a ZIF-8 / SnO2 composite and a preparation method and application thereof. Background Art

[0002] Nitrogen dioxide (NO2) is a major nitrogen-containing pollutant in the atmosphere and one of the key parameters for air quality monitoring in my country. NO2 will spontaneously react with other chemicals in the atmosphere to form acid rain and air pollutants, posing a major ecological threat. For the human body, even low concentrations (about 3ppm) of NO2 can irritate the eyes and lungs, reduce the immunity of the respiratory system and even cause death. Excessive exposure to NO2 in pregnant women may also cause attention damage to infants and young children. Therefore, the widespread deployment and interconnection of accurate and fast NO2 sensors is crucial for data collection and analysis to monitor and solve air pollution.

[0003] At present, the more mature methods for measuring NO2 gas in the atmosphere include spectrophotometry, ion chromatography and chemiluminescence. Spectrophotometry has high accuracy and good stability, but it has high requirements for the preservation of reagents and sample retention time. The operation steps of ion chromatography are simple, but the detection time is long and cannot meet the needs of real-time detection. Chemiluminescence has good sensitivity and a wide linear range, but it is easy to convert other nitrogen oxides into NO at the same time during the conversion of NO2, resulting in measurement errors. Therefore, the accurate detection of low-concentration NO2 gas has always been a challenge in air quality monitoring. We still need to make further optimizations based on existing research to establish a simpler and more efficient NO2 determination method.

[0004] With the advancement of nanotechnology, researchers from various countries have continuously developed air quality monitoring sensor devices based on new nanomaterials. Compared with gas sensors such as spectrophotometry, ion chromatography and chemiluminescence, chemiresistive sensors have attracted extensive research attention due to their unique advantages such as high sensitivity, small size, low cost and easy operation, and have shown great application potential in the field of urban atmospheric environment detection. Among them, electrochemical sensor devices based on metal oxide semiconductor@MOFs composite materials have shown excellent gas sensing performance. However, its further development is still restricted by disadvantages such as high operating temperature and poor selectivity.

[0005] Existing metal oxide-based sensing materials that can realize NO2 sensing have relatively high sensing working temperatures, which can reach 150 degrees Celsius or even 300 degrees Celsius. Chinese patent CN116794118A discloses a NO2 sensor based on In2O3 / ZIF-8 core-shell nanocube composite material and its preparation method, which uses a simple solvent thermal method and in-situ growth method to prepare ZIF-8 filter film-modified In2O3 nanocube composite material, and effectively improves the sensor's specific recognition sensitivity for NO2 by coating the surface with ZIF-8 filter film, but its optimal working temperature is 125°C, which is still relatively high and needs further research. Summary of the invention

[0006] The purpose of the present invention is to provide a ZIF-8 / SnO2 composite and its preparation method and application. The prepared sensor based on the ZIF-8 / SnO2 composite can realize accurate detection of NO2 at low temperature and has high electrochemical responsiveness and selectivity.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] On the one hand, the present invention provides a ZIF-8 / SnO2 composite, which uses mesoporous SnO2 nanospheres as carriers, and the internal pores and surface of the composite are loaded with ZIF-8.

[0009] Preferably, the diameter of the mesoporous SnO2 nanospheres is 690-720 nm, the pore size is 8-9 nm, and the specific surface area is 78-80 m 2 ·g -1 .

[0010] Preferably, the diameter of the ZIF-8 / SnO2 composite is 790-820 nm, the pore size is 7-8 nm, and the specific surface area is 69-71 m 2 ·g -1 .

[0011] Preferably, the mass ratio of the ZIF-8 to the mesoporous SnO2 nanospheres is 1:20-30.

[0012] Further preferably, the mass ratio of the ZIF-8 to the mesoporous SnO2 nanospheres is 1:25.

[0013] In the present invention, the metal oxide semiconductor mesoporous SnO2 nanospheres have good chemical stability and high electrical conductivity, and the ZIF-8 has certain moisture resistance.

[0014] In a second aspect, the present invention further provides a method for preparing the ZIF-8 / SnO2 composite, comprising the following steps:

[0015] S1: Preparation of mesoporous SnO2 nanospheres;

[0016] S2: Preparation of SnO2 / ZIF-8 composite.

[0017] Preferably, the specific steps of step S1 are: prepare F127 solution and tannic acid aqueous solution respectively; mix the tannic acid aqueous solution with the F127 solution, add formaldehyde aqueous solution, and stir continuously at a speed of 300 to 500 rpm for 20 to 28 hours to obtain a tannic acid-F127 mixed solution; prepare a stannous sulfate aqueous solution, and mix it with the tannic acid-F127 mixed solution, and oil bath it at a temperature of 90 to 110 degrees Celsius for 8 to 16 hours to obtain a precursor solution; after centrifugal washing and drying, calcinate at a temperature of 350 to 500 degrees Celsius for 1.5 to 4 hours to obtain the mesoporous SnO2 nanospheres.

[0018] Further preferably, the F127 refers to a polyoxyethylene polyoxypropylene ether triblock copolymer.

[0019] Further preferably, in step S1, the concentration of F127 in the F127 solution is 4.0-5.5 mg / mL.

[0020] Further preferably, in step S1, the F127 solution is obtained by adding F127 to a mixture of deionized water, ethanol and ammonia water and stirring until dissolved, wherein the volume ratio of deionized water, ethanol and ammonia water is 100:(20-30):1, and the concentration of ammonia water is 25-28wt%.

[0021] More preferably, the volume ratio of the deionized water, ethanol and ammonia water is 100:23:1.

[0022] Further preferably, in step S1, the concentration of tannic acid in the tannic acid aqueous solution is 45-60 mg / mL.

[0023] Further preferably, in step S1, the tannic acid aqueous solution is prepared by adding tannic acid into deionized water and dissolving it by ultrasonication.

[0024] More preferably, in step S1, the concentration of formaldehyde in the formaldehyde aqueous solution is 3.7-4.0 wt %.

[0025] Further preferably, in step S1, in the tannic acid-F127 mixed solution, the concentration of tannic acid is 3.0-4.5 mg / mL, and the concentration of F127 is 3.0-4.5 mg / mL.

[0026] Further preferably, in step S1, the concentration of stannous sulfate in the stannous sulfate aqueous solution is 30-40 mg / mL.

[0027] Further preferably, in step S1, the stannous sulfate aqueous solution is obtained by adding stannous sulfate into deionized water and shaking to dissolve.

[0028] Further preferably, in step S1, in the precursor solution, the concentration of F127 is 3.0-4.5 mg / mL, the concentration of tannic acid is 3.0-4.5 mg / mL, and the concentration of stannous sulfate is 0.9-1.5 mg / mL.

[0029] Further preferably, in step S1, the mass ratio of F127, tannic acid and stannous sulfate is 1:1:0.3-1.

[0030] Further preferably, in step S1, the continuous stirring time is 24 hours, and the stirring speed is 300 rpm.

[0031] Further preferably, in step S1, the oil bath time is 12 hours and the temperature of the oil bath is 100 degrees Celsius.

[0032] Further preferably, in step S1, the calcination time is 3 hours and the calcination temperature is 400 degrees Celsius.

[0033] Further preferably, in step S1, deionized water is used for the centrifugal washing.

[0034] Further preferably, in step S1, the drying temperature is 60-70°C, and the drying time is greater than 7 hours.

[0035] Preferably, the specific steps of step S2 are: adding SnO2 to a Zn(NO)3 methanol solution, stirring at a speed of 300 to 500 rpm for 200 to 300 minutes, and centrifuging to obtain a precipitate; adding the precipitate to a 2-methylimidazole methanol solution, stirring at a speed of 300 to 500 rpm for 20 to 28 hours, centrifuging and drying to obtain a ZIF-8 / SnO2 complex.

[0036] Further preferably, in step S2, the concentration of Zn(NO)3 in the Zn(NO)3 methanol solution is 20-30 mg / mL.

[0037] Further preferably, in step S2, the Zn(NO)3 methanol solution is obtained by adding Zn(NO)3·6H2O into a methanol solution and dissolving it by ultrasonication.

[0038] Further preferably, in step S2, the mass volume ratio of SnO2 to Zn(NO)3 methanol solution is 1:5-10.

[0039] More preferably, in step S2, the mass volume ratio of SnO2 to Zn(NO)3 methanol solution is 1:9.

[0040] More preferably, in step S2, the mass volume ratio of the precipitate to the 2-methylimidazole methanol solution is 1:20.

[0041] Further preferably, in step S2, the concentration of 2-methylimidazole in the 2-methylimidazole methanol solution is 40-50 mg / mL.

[0042] Further preferably, in step S2, the 2-methylimidazole methanol solution is obtained by adding 2-methylimidazole to a methanol solution and dissolving it by ultrasonication.

[0043] Further preferably, in step S2, the mass volume ratio of the precipitate to the 2-methylimidazole methanol solution is 1:15-25.

[0044] Further preferably, in step S2, the molar ratio of SnO2, Zn(NO)3·6H2O and 2-methylimidazole is (0.2-1):1:(5-10).

[0045] More preferably, in step S2, the molar ratio of SnO2, Zn(NO)3·6H2O and 2-methylimidazole is 0.2-1:1:7.75.

[0046] Further preferably, in step S2, the centrifugal washing is performed using a methanol solution.

[0047] Further preferably, in step S2, the purity of the methanol solution is 99.5%.

[0048] Further preferably, in step S2, the drying temperature is 60-70°C, and the drying time is greater than 7 hours.

[0049] In a third aspect, the present invention also provides an application of the above-mentioned ZIF-8 / SnO2 composite in the field of nitrogen dioxide sensing.

[0050] Preferably, the ZIF-8 / SnO2 composite can be used as a nitrogen dioxide sensor, the nitrogen dioxide sensor has electrochemical responsiveness, and the nitrogen dioxide sensor can detect nitrogen dioxide at low temperatures.

[0051] Preferably, the low temperature refers to 75-85°C.

[0052] Further preferably, when the low temperature is 80° C., it is the optimal operating temperature of the nitrogen dioxide sensor.

[0053] Further preferably, the nitrogen dioxide sensor is prepared by the following method: dispersing the prepared ZIF-8 / SnO2 complex in ethanol to prepare a suspension; evenly dropping 5 to 15 μL of the suspension on a commercial ceramic tube, and then connecting it to a multimeter to obtain the nitrogen dioxide sensor.

[0054] More preferably, the concentration of the suspension is 1-3 mg / μL.

[0055] More preferably, the volume of the suspension is 10 μL.

[0056] Further preferably, the nitrogen dioxide sensor is used to detect ammonia, comprising the following steps:

[0057] (1) placing the nitrogen dioxide sensor in a nitrogen dioxide atmosphere of known concentration at the operating temperature, detecting the change of the resistance value over time, and drawing a standard working curve;

[0058] (2) placing the sensor in the atmosphere to be measured, and using the standard working curve obtained in step (1) to obtain the nitrogen dioxide concentration in the atmosphere to be measured through the resistance change value.

[0059] More preferably, step (1) comprises the following steps:

[0060] a. placing the nitrogen dioxide sensor in a closed chamber;

[0061] b. Inject nitrogen dioxide into the sealed chamber using an airtight injector, record the resistance change (Rg) indicated by the multimeter, and calculate the corresponding response value;

[0062] c. Obtain the response value of the sensor in different concentrations of nitrogen dioxide by measuring, and draw a curve of response value versus concentration.

[0063] Further preferably, in step b, the response value is calculated by the following method: placing the nitrogen dioxide sensor in a chamber, measuring the resistance at this time by a multimeter connected to the nitrogen dioxide sensor, and obtaining the resistance (Ra) of the sensor in the air; according to the definition formula of the response value S=Rg / Ra, the response value of the sensor at different concentrations is obtained by calculation.

[0064] More preferably, the volume of the sealed chamber is 15-20L.

[0065] More preferably, the volume of the sealed chamber is 20L.

[0066] The high-response nitrogen dioxide sensor based on ZIF-8 modified SnO2 provided by the present invention can detect nitrogen dioxide at a relatively low temperature and has high electrochemical responsiveness, which can avoid the limitation of MOF's application in electrochemical sensing due to its insulating properties, and at the same time reduce the influence of humidity on the sensing material, thereby greatly improving the selective response to nitrogen dioxide.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] (1) The present invention prepares a ZIF-8 / SnO2 composite, using mesoporous SnO2 nanospheres as a carrier, with ZIF-8 loaded in the internal pores and on the surface. The composite can be used as a nitrogen dioxide sensor and has high electrochemical responsiveness and selectivity to nitrogen dioxide at low temperatures.

[0069] (2) The metal oxide semiconductor material SnO2 nanospheres prepared by the present invention have mesopores and a large specific surface area, can be loaded with ZIF-8, have a simple preparation method, good chemical stability and high electrical conductivity, and can be combined with ZIF-8 to break through the insulating properties of MOF that limit its application in electrochemical sensing.

[0070] (3) The ZIF-8 prepared by the present invention has a large specific surface area and a certain moisture resistance. It is loaded into the pores and surface of the SnO2 nanospheres, which can reduce the effect of moisture in the air on the response and increase the active sites for nitrogen dioxide adsorption, thereby enhancing the gas selective responsiveness to nitrogen dioxide.

[0071] (4) The nitrogen dioxide sensor prepared based on the ZIF-8 / SnO2 composite of the present invention can detect nitrogen dioxide in the concentration range of 0.2 ppm to 1 ppm at a relatively low temperature of 80°C, and has good repeatability and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 is a scanning electron microscope image of SnO2 shown in Example 1;

[0073] Figure 2 is a scanning electron microscope image of SnO2 / ZIF-8 shown in Example 1;

[0074] Figure 3 This is the EDS element mapping diagram of SnO2 / ZIF-8 shown in Example 1;

[0075] Figure 4 X-ray diffraction patterns of the mesoporous SnO2 nanospheres, ZIF-8 and SnO2 / ZIF-8 shown in Example 1;

[0076] Figure 5The thermogravimetric diagrams of the mesoporous SnO2 nanospheres and SnO2 / ZIF-8 shown in Example 1;

[0077] Figure 6 The Raman images of the mesoporous SnO2 nanospheres and SnO2 / ZIF-8 shown in Example 1;

[0078] Figure 7 The N2 adsorption curve and pore size distribution diagram of the mesoporous SnO2 nanospheres and SnO2 / ZIF-8 shown in Example 1;

[0079] Figure 8 The graph is a response trend change diagram of SnO2 / ZIF-8 shown in Example 1 to 1 ppm nitrogen dioxide in the range of 36 to 130 degrees Celsius;

[0080] Fig. 9 The graph is the response of SnO2 / ZIF-8 to the gradient nitrogen dioxide concentration shown in Example 1;

[0081] Fig.10 It is a linear fitting diagram of the response value of SnO2 / ZIF-8 to nitrogen dioxide and gas concentration shown in Example 1;

[0082] Fig.11 This is a three-cycle response recovery curve of SnO2 / ZIF-8 to 11 ppb nitrogen dioxide shown in Example 1;

[0083] Fig.12 This is the repeated response diagram of SnO2 / ZIF-8 to 0.5 ppm nitrogen dioxide shown in Example 1;

[0084] Fig.13 This is the gas selection response diagram of SnO2 / ZIF-8 shown in Example 1. DETAILED DESCRIPTION

[0085] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0086] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0087] Example 1

[0088] This embodiment provides a method for preparing a composite material based on ZIF-8 modified SnO2, comprising the following steps:

[0089] S1. Preparation of metal oxide semiconductor (mesoporous SnO2 nanospheres)

[0090] Weigh 200 mg of F127, add it to a mixed solution of 35 mL of deionized water, 8 mL of ethanol and 350 μL of ammonia water (25% to 28% wt), stir until F127 is completely dissolved, weigh 200 mg of tannic acid, add it to 2 mL of deionized water, ultrasonically dissolve it and pour it into the above mixed solution, then add 3.8 mL of 3.7% wt formaldehyde aqueous solution, stir continuously (300 rpm) for 24 hours, then weigh 70 mg of stannous sulfate, add it to 2 mL of deionized water, shake it to dissolve it and pour it into the above mixed solution, oil bath at 100 degrees Celsius for 12 hours, centrifuge it for washing, dry it (70 degrees Celsius), and finally calcine it at a high temperature of 400 degrees Celsius for 3 hours to obtain SnO2.

[0091] Preparation of S2, SnO2 and ZIF-8 composite materials (SnO2 / ZIF-8 composites)

[0092] Weigh 224 mg Zn(NO)3·6H2O, add it to 10 mL methanol, and dissolve it by ultrasonic. Then weigh 25 mg SnO2, add it to the above solution, stir for 250 minutes, and wash it by centrifugation with methanol. Then weigh 479 mg 2-methylimidazole, add it to 10 mL methanol, and dissolve it by ultrasonic. Then add the precipitate obtained by the above centrifugation, stir at room temperature for 12 hours, let it stand for 12 hours, wash it by centrifugation, and dry it (60 degrees Celsius) to obtain the SnO2 complex loaded with ZIF-8.

[0093] 1. Structural characterization of SnO2 / ZIF-8

[0094] The prepared SnO2 was characterized by scanning electron microscopy. Figure 1 As shown, the size of SnO2 in the figure is about 705nm, where the scale bar is 5.0μm.

[0095] The prepared SnO2 / ZIF-8 was characterized by scanning electron microscopy. Figure 2 As shown, the size of SnO2 / ZIF-8 in the figure is about 804nm, where the scale bar is 1.0μm.

[0096] Figure 3 This is the EDS element mapping diagram of SnO2 / ZIF-8. The material mainly contains C, N, O, Sn, and Zn elements. The presence of Zn and N elements is obvious. This is due to the doping of ZIF-8 in the composite material, indicating the successful preparation of SnO2 / ZIF-8.

[0097] Figure 4The X-ray diffraction patterns of mesoporous SnO2 nanospheres, ZIF-8 and SnO2 / ZIF-8 show that SnO2 has good crystallinity and the composite product also has the characteristic peaks of ZIF-8, indicating the successful composite of the materials.

[0098] Figure 5 The thermogravimetric diagrams of mesoporous SnO2 nanospheres and SnO2 / ZIF-8. The thermogravimetric curves show that SnO2 and its composite material with ZIF-8 (SnO2 / ZIF-8) have a small weight loss, indicating that these two materials have good thermal stability. The thermogravimetric curve of the composite material is consistent with that of SnO2, but the weight loss rate is higher than that of SnO2. Calculation shows that the loading rate of ZIF-8 is about 6%.

[0099] Figure 6 The Raman images of mesoporous SnO2 nanospheres and SnO2 / ZIF-8 show that SnO2 has a unique peak at 480 cm -1 、600cm -1 、790cm -1 The three characteristic peaks of SnO2 / ZIF-8 and SnO2 are similar in shape and have a peak at 1500cm -1 The characteristic peaks of ZIF-8 appeared on the left and right, indicating the successful loading of ZIF-8 on the mesoporous SnO2 nanospheres.

[0100] Figure 7 The N2 adsorption curves and pore size distribution of mesoporous SnO2 nanospheres and SnO2 / ZIF-8. After SnO2 was loaded with ZIF-8, the image showed a type IV N2 isothermal adsorption-desorption curve. The pore size decreased from 8.2nm to 7.5nm, and the specific surface area increased from 79.4m 2 / g is reduced to 70.6m 2 / g, indicating that SnO2 nanospheres are indeed mesoporous, and the growth of ZIF-8 in the pores of mesoporous SnO2 nanospheres leads to a decrease in pore size and thus a decrease in specific surface area.

[0101] 2. Electrochemical Sensing Performance of SnO2 / ZIF-8 for Nitrogen Dioxide

[0102] SnO2 / ZIF-8 powder was dispersed in ethanol, and the concentration of SnO2 / ZIF-8 in the suspension was 1mg / μL. Then, 10μL of the suspension was evenly dropped on a commercial ceramic tube and placed in a 20L chamber, and connected to a heater. When detecting nitrogen dioxide gas, nitrogen dioxide was injected into the closed chamber through an airtight injector, and a multimeter was used to indicate the change in resistance. When detecting ammonia and other test liquids, a heater was also required to evaporate ammonia and other test liquids, and a multimeter was used to indicate the change in resistance. All experimental conditions, unless otherwise specified, were tested at a temperature of 80 degrees Celsius and a high ambient humidity (63% to 85%).

[0103] Figure 8 This is a graph showing the response trend of SnO2 / ZIF-8 to 1 ppm nitrogen dioxide in the range of 36 to 130 degrees Celsius, indicating that the optimal operating temperature of the sensor device prepared from SnO2 / ZIF-8 sensing material is 80 degrees Celsius.

[0104] Fig. 9 This is the response diagram of SnO2 / ZIF-8 to gradient nitrogen dioxide concentration. The nitrogen dioxide test concentration ranges from 0.2ppm to 1ppm, and the response degree increases from R g / R a =10.66 increased to 85.95%.

[0105] Fig.10 This is the linear fitting diagram of the response value of SnO2 / ZIF-8 to nitrogen dioxide and the gas concentration. The fitting degree is greater than 0.9, which shows that the response value has a good linear relationship with the gas concentration.

[0106] Fig.11 This is the three-cycle response recovery curve of SnO2 / ZIF-8 to 11ppb nitrogen dioxide, indicating that it does respond to the calculated theoretical detection limit.

[0107] Fig.12 This is the repeated response diagram of SnO2 / ZIF-8 to 0.5ppm nitrogen dioxide. It can be seen that the material maintains good repeated response stability in six cycles.

[0108] Fig.13 This is the gas selection response diagram of SnO2 / ZIF-8. The test objects are 1ppm nitrogen dioxide, 200ppm methanol, ethanol, isopropanol, xylene and ammonia. Among them, nitrogen dioxide, methanol, ethanol, isopropanol, xylene and ammonia are used as interference gases. The results show that the material's response to nitrogen dioxide is much higher than other interference gases.

[0109] In summary, the present invention prepares a ZIF-8 / SnO2 composite, using mesoporous SnO2 nanospheres as carriers, with ZIF-8 loaded in the internal pores and on the surface. The composite can be used as a nitrogen dioxide sensor and has high electrochemical responsiveness and selectivity to nitrogen dioxide at low temperatures.

[0110] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A ZIF-8 / SnO2 composite, characterized in that: Mesoporous SnO2 nanospheres are used as carriers, and ZIF-8 is loaded in their internal pores and on their surfaces.

2. A ZIF-8 / SnO2 composite according to claim 1, characterized in that: The diameter of the mesoporous SnO2 nanospheres is 690-720 nm, the pore size is 8-9 nm, and the specific surface area is 78-80 m 2 ·g -1 The diameter of the ZIF-8 / SnO2 composite is 790-820 nm, the pore size is 7-8 nm, and the specific surface area is 69-71 m 2 ·g -1 .

3. A ZIF-8 / SnO2 composite according to claim 1, characterized in that: The mass ratio of the ZIF-8 to the mesoporous SnO2 nanospheres is 1:20-30.

4. A method for preparing the ZIF-8 / SnO2 composite according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Preparation of mesoporous SnO2 nanospheres; S2: Preparation of SnO2 / ZIF-8 composite.

5. The method for preparing the ZIF-8 / SnO2 composite according to claim 4, characterized in that: The specific steps of step S1 are: prepare F127 solution and tannic acid aqueous solution respectively; mix the tannic acid aqueous solution with the F127 solution, add formaldehyde aqueous solution, and stir continuously at a speed of 300 to 500 rpm for 20 to 28 hours to obtain a tannic acid-F127 mixed solution; prepare a stannous sulfate aqueous solution, and mix it with the tannic acid-F127 mixed solution, and oil bath it at a temperature of 90 to 110 degrees Celsius for 8 to 16 hours to obtain a precursor solution; after centrifugal washing and drying, calcine at a temperature of 350 to 500°C for 1.5 to 4 hours to obtain the mesoporous SnO2 nanospheres.

6. The method for preparing the ZIF-8 / SnO2 composite according to claim 5, characterized in that: In the F127 solution, the concentration of F127 is 4.0-5.5 mg / mL, and in the tannic acid aqueous solution, the concentration of tannic acid is 45-60 mg / mL; The formaldehyde aqueous solution has a formaldehyde concentration of 3.7 to 4.0 wt %; In the tannic acid-F127 mixed solution, the concentration of tannic acid is 3.0-4.5 mg / mL, and the concentration of F127 is 3.0-4.5 mg / mL; In the stannous sulfate aqueous solution, the concentration of stannous sulfate is 30-40 mg / mL; In the precursor solution, the concentration of F127 is 3.0-4.5 mg / mL, the concentration of tannic acid is 3.0-4.5 mg / mL, the concentration of stannous sulfate is 0.9-1.5 mg / mL, and the mass ratio of F127, tannic acid and stannous sulfate is 1:1:0.3-1.

7. The method for preparing the ZIF-8 / SnO2 composite according to claim 5, characterized in that: The F127 solution is obtained by dissolving F127 in a mixture of deionized water, ethanol and ammonia water, wherein the volume ratio of deionized water, ethanol and ammonia water is 100:(20-30):1, and the concentration of ammonia water is 25-28wt%.

8. The method for preparing the ZIF-8 / SnO2 composite according to claim 4, characterized in that: The specific steps of step S2 are: adding SnO2 to Zn(NO)3 methanol solution, stirring at a speed of 300 to 500 rpm for 200 to 300 minutes, and centrifuging to obtain a precipitate; adding the precipitate to a 2-methylimidazole methanol solution, stirring at a speed of 300 to 500 rpm for 20 to 28 hours, centrifuging and drying to obtain a ZIF-8 / SnO2 complex.

9. The method for preparing the ZIF-8 / SnO2 composite according to claim 8, characterized in that: In the Zn(NO)3 methanol solution, the concentration of Zn(NO)3 is 20-30 mg / mL; The mass volume ratio of SnO2 to Zn(NO)3 methanol solution is 1:5-10; In the 2-methylimidazole methanol solution, the concentration of 2-methylimidazole is 40-50 mg / mL; The mass volume ratio of the precipitate to the 2-methylimidazole methanol solution is 1:15-25; The molar ratio of SnO2, Zn(NO)3·6H2O and 2-methylimidazole is (0.2-1):1:(5-10).

10. Use of the ZIF-8 / SnO2 composite according to any one of claims 1 to 3 in the field of nitrogen dioxide sensing.

Citation Information

Patent Citations

  • Preparation method of mesoporous SiOx / C composite negative material of lithium-ion battery

    CN103280560A

  • Preparation method and application of SnO2 / ZIF-8 composite gas-sensitive material

    CN113655097A

  • Platinum-loaded porous tin oxide nanosphere gas-sensitive material as well as preparation method and application thereof

    CN113820363A

  • Meso pore inorganic oxide porous body and production method of the same

    JP2014114193A